Auxilia and gymnasia: A sicilian model of Roman imperialism - Prag, J (Cambridge University Press, 2010)
This paper examines the evidence for military activity in the Republican provincia of Sicily from the Punic Wars to the Civil Wars, and the implications of this for our understanding of Republican Sicily and Republican imperialism. After the Second Punic War there was very little use of Roman or Italian allied soldiers on the island, but extensive use, by Rome, of local Sicilian soldiers. The rich evidence for gymnasia suggests one way in which this use of local manpower was based upon existing civic structures and encouraged local civic culture and identity. These conclusions prompt a reassessment of the importance of auxilia externa under the Roman Republic and of models for Republican imperial control of provinciae.